You are special - Lucado, Max.; Martinez, Sergio, 1937- (New York, NY : Scholastic, 1997)
Punchinello's opinion of himself changes after talking to his creator.
"The text for 'You are special' originally appeared in 'Tell me the secrets' written by Max Lucado and illustrated by Ron DiCianni" -- verso.
Keywords: Self-esteem -- Fiction; Toys -- Fiction; Christian life -- Fiction; Parables